Evaluation of Certain Insecticides against Diamondback Moth (DBM) Plutella xylostella on Cauliflower - Harika, Gudivada; Dhurua, S.; Suresh, M.; Sreesandhya, N. (International Journal of Bio-resource and Stress Management, 2019)
Studies were carried out in field condition during rabi, from November 2017 to February 2018 at Acharya N. G. Ranga Agricultural University, Agricultural College Farm, Naira, to evaluate the efficacy of certain newer insecticides against diamondback moth (DBM) Plutella xylostella on Cauliflower. The findings of the experiment revealed that all the chemicals evaluated against Diamond back moth larvae were significantly superior to check in protecting cauliflower from Diamond Back Moth at 3 and 7 days after treatment. Among all the tested insecticides, Spinosad 45 SC, Indoxacarb 14.5 SC and Emamectin benzoate 5% SG proved to be the most effective treatments in reducing the larval population of Diamond Back Moth. During the study Flubendiamide 39.35 SC and Thiodicarb 70 SP were found moderately effective against Diamond back moth. The treatments Lufenuron 5 EC and Acephate 75 WP were found least effective. The highest marketable yield of Cauliflower heads was recorded in Spinosad 45 SC (228.80 q ha-1). It was followed by Indoxacarb 14.5 SC (219.10 q ha-1) and emamectin benzoate 5% SG, which yielded (193.90 q ha-1) Flubendiamide 39.35 SC, Thiodicarb 70 SP, Lufenuron 5 EC and Acephate 75 WP yielded the lowest marketable yields of 165.90, 145.50, 120.80 and 108.00 q ha-1 respectively. The highest Cost Benefit (C:B) ratio of 69.85 was obtained with the treatment Indoxacarb 14.5 SC followed by Emamectin benzoate 5% SG (60.18), Spinosad 45 SC (30.13) and Flubendiamide 39.35 SC (24.56).